Effects of uncertainty and spousal support on infertility-related quality of life in women undergoing assisted reproductive technologies - Hye Shin Lee; Sunjoo Boo; Jeong-Ah Ahn; Ju-Eun Song (Korean Society of Women Health Nursing, 2020)
Purpose The purpose of this study was to investigate the effects of uncertainty and spousal support on infertility-related quality of life (QoL) in women undergoing assisted reproductive technologies. Methods In this correlational survey study, 172 infertile women undergoing assisted reproductive technologies for infertility treatment at M hospital in Seoul participated. Data collection took place at the outpatient department of M hospital using a self-report questionnaire from July to August 2019. Data were analyzed using SPSS for Windows version 28.0. Results The mean scores for uncertainty, spousal support, and infertility-related quality of life (QoL) were 28.35 (out of 50), 86.67 (out of 115), and 57.98 (out of 100), respectively. Infertility-related quality of life (QoL) was positively correlated with spousal support and negatively correlated with uncertainty. According to the regression analysis, infertility-related quality of life (QoL) was significantly affected by uncertainty, total number of assisted reproductive technology treatments, marriage duration, subjective health status, the financial burden of infertility testing, and the presence of a burdensome person. These variables had an explanatory power of 35.0% for infertility-related quality of life (QoL). Conclusion Uncertainty was an important factor influencing infertility-related quality of life (QoL) among women undergoing assisted reproductive technologies. It is necessary to develop and implement a nursing intervention program focused on reducing various forms of uncertainty during assisted reproductive procedures and to consider other factors affecting infertility-related quality of life (QoL) in the clinical setting.